OPTIMASI PENCAMPURAN BATUBARA DENGAN MENGGUNAKAN METODE TRIAL AND ERROR UNTUK MEMENUHI STANDAR BATUBARA PLTU SAWAHLUNTO STUDI KASUS PT. CAHAYA BUMI PERDANA - Rizki Agusta Yusra; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Coal is a sedimentary rock formed from homogeneous organic deposits. Coal is spread in layers and each layer has a different quality. Due to the difference in quality at each coal seam, the coal blending process needs to be done to meet market needs. PT. Cahaya Bumi Perdana is a coal mining company located in Sawahlunto City, West Sumatra. PT. Cahaya Bumi Perdana does mining with underground mining method. In underground mining, the BT 04 tunnel and the BT 06 tunnel have different calories because they are located on different seams. The calories in the BT 04 tunnel have high quality fine coal with a calorific value of 6,183 Kcal / Kg and the calories in the BT 06 tunnel have high quality coarse coal with a calorific value of 7,795 Kcal / Kg. Meanwhile, consumer demand is 6,300 Kcal / Kg. Due to the coal calories that are not in accordance with consumer demand, a blending process is required. In this study, the method used for the blending process is trial and error method. In this research, there are 4 parameters used for testing coal quality, namely ash content (AC), volatile matter (VM), total sulfur (TS) and calorie value (CV). This coal quality parameter is determined by consumer demand with a value of ash content (AC) with a maximum value of 14%, volatile matter (VM) with a maximum value of 36.60%, total sulfur (TS) with a value of less than 1%, calorie value (CV ) with a value of 6,300 Kcal / Kg with a tonnage of 2,000 tons. The results of the study are based on laboratory tests conducted by PT. Cahaya Bumi Perdana is the value of ash content (AC) with a maximum value of 13,93%, volatile matter (VM) with a maximum value of 35.202%, total sulfur (TS) with a small value of 0.3965%, calorie value (CV) with a value of 6,577.9 Kcal / Kg with a ratio of high-quality fine coal tonnage 1,510 tons and high-coarse coal tonnage 490 tons or with a ratio of 3:1. There is a slight difference between the calculation using the trial and error method that the author did. The calculation result that passes consumer demand is the calorific value (CV), which 6,577.9 Kcal/Kg through 6,300 Kcal/Kg consumen demand. For this difference in calorific value, will be returned to the agreement between the company and the consumer.Keywords: Coal, trial and error, coal quality